The Use and Development of the Xinkan Languages - Rogers, Chris (University of Texas Press, 2021)
Once spoken only in Santa Rosa Department, Guatemala, the Xinkan language family is unique within Mesoamerica, comprising four closely related languages that are unrelated to any of the other language groups used within the region. Descriptions of Xinkan date to 1770 but are typically only sketches or partial word lists. Not even the community of indigenous people who identify as Xinka today-the last speakers-have had access to a reliable descriptive source on their ancestral tongue. Preserving this endangered communication system in accurate, thorough detail, The Use and Development of the Xinkan Languages presents a historical framework, internal classifications, and both synchronic and diachronic descriptions, incorporating all elements of grammar based on extensive unpublished data collected in the 1970s by Lyle Campbell and Terrence Kaufman. This valuable contribution is enhanced by author Chris Rogers's emphasis on contextualizing the findings. Introducing the languages, Rogers presents important information regarding the social and cultural milieu of the speakers. He also traces a phonological reconstruction of Proto-Xinkan and reconstructs historical morphology and syntax. These revelations are of particular interest because the development of Xinka and the many aspects of Xinka morphosyntax have not been well understood. A sample text, "Na Mulha Uy," is included as well. Solving numerous complex, centuries-old linguistic puzzles, The Use and Development of the Xinkan Languages unlocks new potential for the rediscovery of a rich cultural history